Steels metallurgy and applications - Llewellyn, D. T. (Butterworth-Heinemann, 1998)
STEELS provides a metallurgical understanding of commercial steel grades and the design, manufacturing and service requirements that govern their application. The properties of different steels are described, detailing the effect of composition, processing and heat treatment. Where appropriate an introduction is given to standard specifications and design codes provided on component manufacture and property requirements for successful service performance. The book deals with steel products in some depth, in four chapters covering wide strip, structural steels, engineering and stainless steel grades. At the begining of each chapter an overview is given which details important features of the grades and a historical perspective of their development. Also featured are up to date information on steel prices and specifications.-David Llewellyn has over thirty years experience in the steel industry and is currently lecturing in the Materials Engineering Department at University College Swansea. '.the book unfolds into an easily readable and a valuable source of highly relevant and contemporary information on steels' - METALS AND MATERIALS '. a high quality product from all points of view' - INSTITUTE OF METALS AND MATERIALS AUSTRALASIA features up to date information on steel prices and specifications. STEELS provides a metallurgical understanding of the commercial steel grades and the design, manufacturing and service requirements that govern their application. The properties of different steels are described, detailing the effect of composition, processing and heat treatment. Where appropriate an introduction is given to standard specifications and design codes provided on component manufacture and property requirements for successful service performance.-The book deals with steel products in some depth, in four chapters covering wide strip, structural steels, engineering and stainless steel grades. At the begining of each chapter an overview is given which details important features of the grades and a historical perspective of their development. Also featured are up to date information on steel prices and specifications. David Llewellyn has over thirty years experience in the steel industry and is currently lecturing in the Materials Engineering Department at University College Swansea. '.the book unfolds into an easily readable and a valuable source of highly relevant and contemporary information on steels' - METALS AND MATERIALS '. a high quality product from all points of view' - INSTITUTE OF METALS AND MATERIALS AUSTRALASIA.
Keywords: Steel -- Metallurgy.; Steel alloys -- Metallurgy.; elektronické knihy; electronic books